522 THE IMPACT OF SPECIALIST CARDIOLOGY INPUT ON OUTCOMES IN PATIENTS ADMITTED FOR HEART FAILURE WITH NORMAL EJECTION FRACTION. A MULTICENTRE STUDY. (15th December 2022) - Cannata, Antonio; Badawy, Layla; Anyu, Anawinla Ta; Samways, Jack; Sweeney, Mark; Zackeri, Rosita; Scott, Paul; Piper, Susan; Plymen, Carla; Mcdonagh, Theresa; Bromage, Daniel
Abstract: Aims: Specialist cardiology care is associated with a prognostic benefit in patients with HF with reduced ejection fraction (HFrEF) admitted with decompensated heart failure (HF). However, up to one third of patients admitted with HF and normal ejection fraction (HFnEF) do not receive specialist cardiology input. Whether this has prognostic implications is unknown. Methods: Data on patients hospitalised with HFnEF from two tertiary centres were analysed. The primary outcome measure was all-cause mortality during follow-up. The secondary outcome was in-hospital mortality. Results: A total of 1, 413 patients were included in the study. Of these, 23% (n=322) did not receive in-hospital specialist cardiology input. Patients seen by a cardiologist were less likely to have hypertension (73% vs 79%, p=0.03) and respiratory comorbidities (25% vs 31%, p=0.02) compared to those who did not receive specialist input. Similarly, clinical presentation was more severe for those who received specialist input (NYHA III/IV 83% vs 75% respectively, p=0.003; moderate-to-severe peripheral oedema 65% vs 54%, p<0.001). Medical management was similar, except for a higher use of diuretics (90% vs 86%, p=0.04) and a longer length of stay for patients who received specialist input (9 vs 4 days, p<0.001). Long-term outcomes were comparable between patients who received specialist input and those who did not. However, specialist input was independently associated with lower in-hospital mortality (HR 0.19, CI 0.09-0.43, p<0.001). Conclusion: In-hospital cardiology specialist input has no long-term prognostic advantage in patients with HFnEF but it is independently associated with reduced in-hospital mortality.